2021
DOI: 10.1093/brain/awab157
|View full text |Cite
|
Sign up to set email alerts
|

Motor and cognitive outcomes of cerebello-spinal stimulation in neurodegenerative ataxia

Abstract: Cerebellar ataxias represent a heterogeneous group of disabling disorders characterized by motor and cognitive disturbances, for which no effective treatment is currently available. In this randomized, double-blind, sham-controlled trial, followed by an open-label phase, we investigated whether treatment with cerebello-spinal transcranial direct current stimulation (tDCS) could improve both motor and cognitive symptoms in patients with neurodegenerative ataxia at short and long-term. Sixty-one patients were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 50 publications
4
42
0
Order By: Relevance
“…A potential way to confirm this hypothesis could be through resting state connectivity (rsFC) in FRDA patients. Indeed, ctDCS has been found recently to improve cognitive performances in a population of patients (one FRDA) with cerebellar ataxia of mixed origins [ 65 ], supporting the role of the cerebellum in their modulation.…”
Section: Discussionmentioning
confidence: 97%
“…A potential way to confirm this hypothesis could be through resting state connectivity (rsFC) in FRDA patients. Indeed, ctDCS has been found recently to improve cognitive performances in a population of patients (one FRDA) with cerebellar ataxia of mixed origins [ 65 ], supporting the role of the cerebellum in their modulation.…”
Section: Discussionmentioning
confidence: 97%
“…When restricted to the two studies with unique NCT identifiers at http://clinicaltrials.gov [16,17], the total sample size was 81, and the meta‐analytic estimates remained similar to the results reported above. CBI was found to remain significantly reduced at an MD of −0.36% (95% CI −0.39 to −0.32, p < 0.001) but with significant heterogeneity ( I 2 = 82%, p for Cochran's Q test 0.019).…”
Section: Resultsmentioning
confidence: 53%
“…Another three studies involving 101 patients reported a poststimulation change in CBI (Figure 1b) [16][17][18], and the randomeffects analysis found post-treatment improvement to be an MD of −0.34% (95% CI −0.37 to −0.32, p < 0.001), with substantial heterogeneity detected (I 2 = 79%, p for Cochran's Q test 0.009). Despite the high heterogeneity observed for the change in CBI, no notable differences were noticed with regard to baseline characteristics of the patient population (type of neurodegenerative ataxia, age and proportion of females included).…”
Section: Meta-analysis Of Outcomesmentioning
confidence: 99%
“…Three randomized controlled trials from the same group have recently demonstrated substantial clinical improvement in ataxia patients with mixed etiologies following a two-week regimen of daily cerebellar anodal or cerebello-spinal tDCS sessions [ 19 21 ]. In the first two studies, the reported reduction in ataxia severity was found to persist throughout the three-month follow-up period, accompanied by a restoration of functional cerebellothalamocortical tract connectivity [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the first two studies, the reported reduction in ataxia severity was found to persist throughout the three-month follow-up period, accompanied by a restoration of functional cerebellothalamocortical tract connectivity [ 20 , 21 ]. In their third study, the investigators extended the randomized, double-blind phase with an open-label phase, demonstrating the add-on effect of a second round of cerebello-spinal tDCS after three months on both motor and cognitive outcomes [ 19 ]. Albeit encouraging, further trials are required to evaluate the effects of similar treatment protocols in etiologically homogeneous cohorts.…”
Section: Introductionmentioning
confidence: 99%